Removal of chromium from aqueous solution - Lee, C.K.; Low, K.S.; Kek, K.L. (Elsevier Science, 1995)
Laboratory studies were conducted to assess the ability of natural moss and copper-coated moss to remove Cr(III) and Cr(VI) from aqueous solutions. Parameters investigated included pH, contact time, initial concentration, sorbent dosage and temperature. Application of the Langmuir isotherm to the systems yielded maximum sorption capacities of 18·9 and 7·1 mg/g for Cr(III) and Cr(VI), respectively. In addition, a series of flow studies was carried out using columns containing a mixture of natural and copper-coated moss. Results indicated that the treatment of aqueous solutions containing a mixture of Cr(III) and Cr(VI) using such a column is feasible.